Transport and thermodynamical properties of Yb(Cu,Al)5 compounds - Bauer, E. (1992)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina